2006
DOI: 10.1002/gcc.20312
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of doxorubicin‐resistant neuroblastoma cell lines: Evidence that acquired multidrug resistance results from a unique large amplification of the 7q21 region

Abstract: Neuroblastoma is a heterogeneous neural crest-derived embryonic childhood neoplasm that is the second most common solid tumor found in children. Despite recent advances in combined therapy, the overall survival of patients with high-stage disease has not improved in the last decades. Treatment failure is in part attributed to multidrug resistance. To address the mechanisms involved in the development of multidrug resistance, we have generated two doxorubicin-resistant neuroblastoma cell lines (IGRN-91R and LAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…We have recently reported that DoxR NB cell lines exhibited overexpression of the MDR1 gene due to an amplification at the 7q21 locus. As the MDR1/P-gp inhibitor verapamil was not able to restore 100% of cell sensitivity to DoxR, etoposide or paclitaxel, we postulated that P-glycoprotein-mediated drug efflux was not responsible for 100% drug resistance (Flahaut et al, 2006b). In this study, microarray expression profile analysis of resistant variants revealed 7q21 region-related amplification and overexpression of several genes, including MDR1 and the Wnt receptor FZD1.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…We have recently reported that DoxR NB cell lines exhibited overexpression of the MDR1 gene due to an amplification at the 7q21 locus. As the MDR1/P-gp inhibitor verapamil was not able to restore 100% of cell sensitivity to DoxR, etoposide or paclitaxel, we postulated that P-glycoprotein-mediated drug efflux was not responsible for 100% drug resistance (Flahaut et al, 2006b). In this study, microarray expression profile analysis of resistant variants revealed 7q21 region-related amplification and overexpression of several genes, including MDR1 and the Wnt receptor FZD1.…”
Section: Introductionmentioning
confidence: 64%
“…Interestingly, FZD1 encoding the frizzled 1 receptor, a seven transmembrane receptor member of the Wnt/b-catenin signalling pathway was found to be the highest upregulated transcript (34.5-fold stimulation) in resistant cells. Moreover, 12 out of 16 transcripts in the list of upregulated transcripts corresponded to genes located on the 7q21 region as published earlier (Flahaut et al, 2006b). As the 7q21 amplified region also harbours the FZD1 gene, we now investigated whether the two MDR1 and FZD1 genes were coamplified.…”
Section: Identification Of Differentially Expressed Genes In Chemoresmentioning
confidence: 77%
See 3 more Smart Citations